Stereoelectroencephalography electrode placement: Detection of blood vessel conflicts. (22nd July 2019) - Li, Kuo; Vakharia, Vejay N.; Sparks, Rachel; Rodionov, Roman; Vos, Sjoerd B.; McEvoy, Andrew W.; Miserocchi, Anna; Wang, Maode; Ourselin, Sebastien; Duncan, John S.
Abstract: Objective: Various forms of vascular imaging are performed to identify vessels that should be avoided during stereoelectroencephalography (SEEG) planning. Digital subtraction angiography (DSA) is the gold standard for intracranial vascular imaging. DSA is an invasive investigation, and a balance is necessary to identify all clinically relevant vessels and not to visualize irrelevant vessels that may unnecessarily restrict electrode placement. We sought to estimate the size of vessels that are clinically significant for SEEG planning. Methods: Thirty‐three consecutive patients who underwent 354 SEEG electrode implantations planned with computer‐assisted planning and DSA segmentation between 2016 and 2018 were identified from a prospectively maintained database. Intracranial positions of electrodes were segmented from postimplantation computed tomography scans. Each electrode was manually reviewed using "probe‐eye view" with the raw preoperative DSA images for vascular conflicts. The diameter of vessels and the location of conflicts were noted. Vessel conflicts identified on raw DSA images were cross‐referenced against other modalities to determine whether the conflict could have been detected. Results: One hundred sixty‐six vessel conflicts were identified between electrodes and DSA‐identified vessels, with 0‐3 conflicts per electrode and a median of four conflicts per patient. The median diameter of conflicting vessels was 1.3 mm (interquartile range [IQR] = 1.0‐1.5 mm). The median depth of conflict was 31.0 mm (IQR = 14.3‐45.0 mm) from the cortical surface. The addition of sulcal models to DSA, magnetic resonance venography (MRV), and T1 + gadolinium images, as an exclusion zone during computer‐assisted planning, would have prevented the majority of vessel conflicts. We were unable to determine whether vessels were displaced or transected by the electrodes. Significance: Vascular segmentation from DSA images was significantly more sensitive than T1 + gadolinium or MRV images. Electrode conflicts with vessels 1‐1.5 mm in size did not result in a radiologically detectable or clinically significant hemorrhage and could potentially be excluded from consideration during SEEG planning.